Strength and behaviour of lightweight ferrocement-aerated concrete sandwich blocks - Memon, Noor Ahmed; Radin Sumadi, Salihuddin; Ramli, Mahyuddin (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2006)

(untitled)
Results of an experimental investigation on sandwich blocks fabricated using lightweight aerated concrete encased in a ferrocement box are presented in this paper. The primary variables investigated are the type of wire mesh; chicken and square wire mesh, and number of wire mesh layers in the ferrocement box. The response variables considered include compressive strength, overall unit weight and failure mode. The results are compared with control block specimens made solely of the aerated concrete. The results showed significant increases in compressive strength due to the encasement of aerated concrete. Overall, the unit weight of the sandwich blocks comply with the specifications for lightweight structural components. The ferrocement encasement changes the otherwise brittle failure mode of aerated concrete into a ductile one